Analisis Perjanjian Perkawinan sebagai Instrumen Kesadaran Hukum: Studi di Kantor Urusan Agama Slawi, Kabupaten Tegal - Amin Wahyu Faozi; Muhammad Latif Fauzi (AHKAM, 2026)
Although legal sources regarding the registration of marriage agreements are available, the practice of registering them at the KUA remains relatively low because, in the current social context, marriage agreements are still regarded as taboo. This condition indicates a gap between the existence of legal regulations and the level of public understanding of those regulations. This study aims to analyze the factors underlying prospective brides and grooms in deciding whether or not to make a marriage agreement, as well as to examine marriage agreements from the perspective of the theory of maqashid syariah and Soerjono Soekanto’s theory of legal awareness. This study employed an empirical juridical method with a qualitative research type. Primary data were obtained through interviews with prospective brides and grooms as well as couples who made marriage agreements at the KUA, while secondary data were derived from journals, books, academic literature, and the results of previous studies. The results showed that the low practice of marriage agreements indicates that public awareness of the law on marriage agreements is still low and that perceptions regarding the benefits that can be obtained are not yet strong. These findings affirm that the low practice of making marriage agreements not only reflects the limited legal literacy of the community, but also shows that understanding of the values of kemaslahatan intended to be realized by the sharia has not yet been optimal. This study contributes to strengthening the study of Islamic family law, particularly in understanding the relationship among legal awareness, kemaslahatan, and the practice of marriage agreements in society.